Pendekatan Psikodinamika Dalam Konseling Kelompok - Bakhrudin All Habsy; Raissa Sekar Nurpuri (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
The psychodynamic group counseling approach considers the intrapsychic and interpersonal dynamics within the group as the main focus of intervention. The main goal of psychodynamic group counseling is to explore and understand unconscious conflicts and underlying patterns of behavior. In psychodynamic group counseling, the counselor acts as a facilitator who helps group members explore unconscious conflicts and dynamics that may arise in group interactions. Through this process, group members are given the opportunity to explore their experiences, identify disturbing patterns, and develop a deeper understanding of themselves. Psychodynamic group counseling methods can involve symbolic interpretation, mimicry analysis, and reflection on interactions between group members. Through discussion and reflection, group members can support each other and explore a deeper understanding of themselves and their relationships with others. As such, psychodynamic group counseling can be a powerful tool in facilitating personal and interpersonal growth for individuals involved in the process. Through a deeper understanding of psychodynamic dynamics in a group context, group members can experience positive changes in their patterns of behavior and improve the quality of their relationships with others.